2011
DOI: 10.4061/2011/561342
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antiplasmodial Activity and Cytotoxicity of Extracts of Selected Medicinal Plants Used by Traditional Healers of Western Cameroon

Abstract: Medicinal plants play a key role in malaria control in Africa, especially in remote areas where health facilities are limited. In order to assess their acclaimed potentials, eleven extracts were prepared from seven selected plants commonly used in Western Cameroon, and tested both for their antiplasmodial activity and cytotoxicity. The antiplasmodial activity was assessed using Lactate Dehydrogenase Assay (pLDH) and the cytotoxicity estimated on LLC-MK2 monkey kidney epithelial cells. Seven extracts from five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…The effect against T. b. brucei was similar to previous reports on H. acida, C. sieberiana, and T. emetica [9]. In contrast to the strong antiplasmodial activity of Guinean V. guineensis, the apolar and polar extracts of the stem bark of V. guineensis from Cameroon exhibited weak activities against both chloroquine-sensitive and multiresistant strains of P. falciparum [10]. Moreover, the methanolic extracts of the leaves and stem bark of V. orientalis from Tanzania were reported to be inactive against multidrug resistant P. falciparum strain K1 [11].…”
supporting
confidence: 86%
“…The effect against T. b. brucei was similar to previous reports on H. acida, C. sieberiana, and T. emetica [9]. In contrast to the strong antiplasmodial activity of Guinean V. guineensis, the apolar and polar extracts of the stem bark of V. guineensis from Cameroon exhibited weak activities against both chloroquine-sensitive and multiresistant strains of P. falciparum [10]. Moreover, the methanolic extracts of the leaves and stem bark of V. orientalis from Tanzania were reported to be inactive against multidrug resistant P. falciparum strain K1 [11].…”
supporting
confidence: 86%
“…µg/ml against P. falciparum 3D7 strain (Zofou et al, 2011). These sesquiterpene lactones may be responsible for the observed inhibition of gametocyte viability by the crude acetone extract of A. afra.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have shown that the plants was multipurpose species in African folk medicine in the treatment of several diseases conditions. D. edulis exhibits considerably antiemetic, antiplasmodial, antidrepanocytary, (anti-sickle cell anaemia) antiinflammatory, antifungal (dermal) effect and F. exasperata is known for its anti-leishmanial, antidiabetic, anticonvulsant, antiinflammatory, antimicrobial, hypolipidemic, antioxidant, antiulcer, anxiolytic and hypotensive activities [17,25,[29][30][31] .…”
Section: Discussionmentioning
confidence: 99%